The Development of the Degrees of Freedom Scale - (:unkn) unknown (My University, 2022)
The Theory of Work Adjustment (TWA) is a person-environment fit model used to predict turnover intention, determined by the satisfaction of one’s values being reinforced at work. A unique component of this framework looks at how one responds when work values are not being met: either by trying to change the outcome with the workplace or adjust oneself to the outcome. What is unknown however, are the factors that influence the different responses. There is evidence to suggest that there are objective external factors that might play a role in these decisions. This study aimed to capture these factors using an Exploratory Factor Analysis (EFA). Results showed a two-factor structure that partially supports the hypothesis that there are five external factors. Implications of these findings are discussed.
Keywords: Adjustment styles; External pressures; Job Demand; Scale development; Theory of work adjustment; Vocational psychology